Violence in Agora's Movie (2009) Directed By Alejandro Amenabar : A sociological Approach - SASONGKO, DONI (2012)
The major problem in this research paper is to explain How Violence in Agora Movie. The purposes of this research paper are to analyze Violence in Agora Movie Movie (2009) based on the structural elements of the movie. To describe Violence in Agora Movie (2009) based on sociological approach. The object study is Agora movie that the movie of Agora Movie by Alenjandro Amenabar. It is using by sociological approach. In analyzing this study, the writer uses qualitative methodology of research and sociological approach. The Primary data source of this research is the movie Agora movie that movie by Alenjandro Amenabar and synopsis of Agora movie. The secondary data sources are the author's biography, essay, comment, homepage, and website about the movie and other relevant sources. Based on the sociological analysis, in Agora movie, Alejandro Amenabar describes how the violence causes the story becoming interesting. Because in the Agora the most prominent film, it is aspects of religion and culture, which can be seen community of alexandria at the 4th century, using the stoning to punish someone who make a mistake or violate the rules of religion and the goverment. It is one evidence of a culture that is being used the Alexandria and Egypt. The structures of Agora movie contains social, political, religious, cultur, economic and science and technology dimensions can be concluded in Agora movie.